2009
DOI: 10.1161/circulationaha.108.793745
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Primary Percutaneous Coronary Intervention and Fibrinolytic Therapy in ST-Segment-Elevation Myocardial Infarction

Abstract: Background-Published meta-analyses comparing primary percutaneous coronary intervention with fibrinolytic therapy in patients with ST-segment-elevation myocardial infarction include only randomized controlled trials (RCTs). We aim to obviate the limited applicability of RCTs to real-world settings by undertaking meta-analyses of both RCTs and observational studies. Methods and Results-We included all RCTs and observational studies, without language restriction, published up to May 1, 2008. We completed separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(88 citation statements)
references
References 61 publications
(73 reference statements)
0
78
0
7
Order By: Relevance
“…6 More recent data have shown trends to improved results with rescue PCI in patients with no evidence of reperfusion after fibrinolytic treatment, as well as routine coronary angiography within hours of the administration of fibrinolytic treatment, even when fibrinolysis appears successful. [7][8][9][10][11] The Comparison of Angioplasty and Prehospital Thrombolysis in Acute Myocardial Infarction (CAPTIM) trial, although underpowered, has suggested that prehospital fibrinolytic therapy with the patients brought to PCI-capable centers and with one third undergoing rescue angioplasty could do at least as well as primary PCI up to 5 years after the initial episode, 12 and a pooled analysis of the CAPTIM and Which Early ST-Elevation Myocardial Infarction Therapy (WEST) trials found a reduction in 1-year mortality with fibrinolysis in patients seen early.…”
Section: Discussionmentioning
confidence: 99%
“…6 More recent data have shown trends to improved results with rescue PCI in patients with no evidence of reperfusion after fibrinolytic treatment, as well as routine coronary angiography within hours of the administration of fibrinolytic treatment, even when fibrinolysis appears successful. [7][8][9][10][11] The Comparison of Angioplasty and Prehospital Thrombolysis in Acute Myocardial Infarction (CAPTIM) trial, although underpowered, has suggested that prehospital fibrinolytic therapy with the patients brought to PCI-capable centers and with one third undergoing rescue angioplasty could do at least as well as primary PCI up to 5 years after the initial episode, 12 and a pooled analysis of the CAPTIM and Which Early ST-Elevation Myocardial Infarction Therapy (WEST) trials found a reduction in 1-year mortality with fibrinolysis in patients seen early.…”
Section: Discussionmentioning
confidence: 99%
“…Perkütan koroner girişim ile TT'yi karşılaştıran çok sayıda randomize çalışma ve gözlemsel çalışmalardan yapılmış bir meta-analizde, randomize çalışmalarda, PKG ile gerek kısa gerekse uzun dönemde tutarlı ölüm oranı yararları olduğu gösterilmekte iken, gözlemsel çalışmaların meta-analizinde erken dönemde göz-lenen yararların uzun dönemde görülmediği saptanmıştır (16) . Bu sonuçlara dayanarak, STEMI'de tercih edilen tedavi şekli PKG olsa da, ulaşım, acil servisteki beklemeler ve kateterizasyon laboratuvarının hazırlanması gibi nedenlerle tedavi gecikmektedir.…”
Section: Discussionunclassified
“…Metoda pPCI u odnosu na fibrinolitiËku terapiju znaËajno smanjuje ukupnu kratkoroËnu smrtnost (7% naspram 9%), nefatalni reinfarkt (3% naspram 7%), moaedani udar (1% naspram 2%) te u zajedniËki ishod od smrti, nefatalnog reinfarkta te moaedanog udara (8% naspram 14%), a bolji rezultati pPCI su perzistirali i na dugoroËnom praÊenju. Huyn i sur 4 su 2009. objavili noviju metaanalizu usporedbe pPCI i fibrinolitiËke terapije koja osim 23 RCT ukljuËuje i 32 opservacijske studije. Opservacijske studije obuhvaÊaju puno veÊi broj bolesnika i time su sveobuhvatnije i realnije predstavljaju svakodnevnu praksu.…”
Section: Usporedba Primarne Perkutane Koronarne Intervencije S Fibrinunclassified